2002
DOI: 10.1002/dc.10157
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of women with atypical squamous cells of undetermined significance (ASCUS)

Abstract: ASCUS is the most common epithelial abnormality diagnosed in cytology laboratories in the US. Recently, the clinical importance of this diagnosis has been seriously questioned, with some investigators advocating elimination of this diagnostic category. This might be inappropriate if the ASCUS designation does define a population that is at significant risk for the development of dysplasia. Cytology and surgical pathology reports for all patients diagnosed as ASCUS in our laboratory during 1990 were reviewed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 49 publications
4
26
0
2
Order By: Relevance
“…27 As the definition of ASCUS has emphasized exclusion criteria rather than what criteria should be included in the category, it is inevitable that poorly sampled HSIL is interpreted as ASCUS. These facts have forced the introduction of new diagnostic criteria that can distinguish atypical squamous cells from HSIL (ASC-H) in the 2001 Bethesda system.…”
Section: Discussionmentioning
confidence: 99%
“…27 As the definition of ASCUS has emphasized exclusion criteria rather than what criteria should be included in the category, it is inevitable that poorly sampled HSIL is interpreted as ASCUS. These facts have forced the introduction of new diagnostic criteria that can distinguish atypical squamous cells from HSIL (ASC-H) in the 2001 Bethesda system.…”
Section: Discussionmentioning
confidence: 99%
“…This increased the proportion of women with CIN 2/3 or ICC to 10.7% at the end of the 7-year follow-up. Raab et al found that at the 6-year follow-up, CIN 2/3 had developed in 9% of women with ASCUS, 16 while a study by Emerson 17 found 10%.…”
Section: Cin/icc Diagnosed During Long-term Follow-upmentioning
confidence: 99%
“…[12][13][14][15] Long-term, population-based follow-up studies of women with an ASCUS Pap smear are fewer, but Raab et al found CIN 2/3 in 9.0% of women after 6 years of follow-up, with 80% diagnosed within the first 2 years of follow-up, 16 similar to the results found by Emerson et al in a 9-year follow-up study. 17 As much as 60% of women with an ASCUS Pap smear might harbor an underlying lesion at the time of the smear, but only approximately 10% will develop CIN 2/3. Hence, most CIN lesions will regress spontaneously, [18][19][20][21][22] and effective follow-up strategies are needed to identify the minority of women who have clinically significant disease while avoiding excessive follow-up evaluation for others.…”
Section: Of Being Diagnosed With Histologically Verified Cin 2/3 or Imentioning
confidence: 99%
“…Emerson et al (13) analysed 15860 patients with cervical cytology a period of 9 years. Patients with previous dysplasia or carcinoma were excluded from analysis.…”
Section: Discussionmentioning
confidence: 99%